D'Elia Naturals Rice Innovation Becomes a New Scrub in the Cosmetics Industry - Pahrul Pahrul; Ika Wisudawaty; Wulan Purnamasari; Mahmuddin Mahmuddin; Uqbah Al Ansyari (PT. Global Research Collaboration, 2025)
Innovation in the cosmetic industry also focuses on the importance of low-cost, domestic, and high-quality products. Beras, such as a local food in Indonesia, contain many nutrients that promote healthy skin, such as vitamin E, dietary fiber, and antioxidants. Penelitian this is a vital choice of products lulur basis as an alternative cosmetic ingredient that has potential. A method of mixing the extraction process and adjusting the yield from beberapa local varieties, which is then formulated with basic flavors such as madu, minyak olive, and various herbal extracts. Uji laboratory and uji application menusjukkan bahwa lulur berbahan dasar beras mampu mengangkat cell kulit mati, melembapkan kulit, serta meningkatkan kecerahan alami kulit. For example, this formula does not cause irritation and sesuai for most types of skin. Pengembangan lulur berbahan dasar beras juga memberikan nilai tambah bagi sektor pertanian local and mendukung concept economy works. This innovation is also based on the cosmetics industry to create products based on sumber daya local that resembles daya saing global. With that, beras not only serve as a meal, but also as a home in products that are cheap and effective.